ANALISIS PERANAN DINAS PERHUBUNGAN DALAM MENINGKATKAN KUALITAS PELAYANAN ANGKUTAN KOTA - Meri Bua Palindangan; Yahya Nusa (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims to determine the role of the transportation department in improving the quality of city transportation services. The research method used is descriptive research, which is research that aims to determine the relationship between 3 variables. In this research, the data collection methods used were interviews, questionnaires and documentation. To determine the role of the transportation department in influencing the quality of city transportation, the Source Triangulation analysis tool is used. The research results show that the quality of city transportation services at the Mimika Regency Transportation Service is still relatively poor. The quality of this service can be seen from the Transportation Service's service functions as regulations, facilities and evaluation. This is proven by the 3 variables analyzed, there are only 2 variables where the level of service is considered good and satisfactory to the community, namely determining the number of transport fleets and building road infrastructure that supports the route. There is only one level of service that is not satisfactory but can still be tolerated, namely the determination of public transport fares